BISNIS PERSEWAAN KELUARGA DALAM NASKAH DRAMA TELEVISI KAZOKU KASHIMASU â€“ FAMILY COMPLEX: KAJIAN SOSIOLOGI SASTRA - Pradityasari, Maya (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2016)
The turning of Japaneses family system Ie into Kazoku Kaku affected negatively on the process of interaction and communication within the members of the family, with the neighborhood and among the members of society. In turn, it brought about the idea of family rental business in Japan. Nipon TV aired a television drama which portrayed this social phenomenon entitled â€œKazoku Kashimasu-family Complex. This article is exploring the cause of the emergence of this phenomenon as seen the TV drama. This study applied sociological approach. The data in this research are scenes and conversations in a play entitled â€œKazoku Kashimasu-family Complexâ€. The analysis shows that one factor causing the phenomenon of family rental business is the divorce that resulted in the single parent or a single parent. Another factor is the familyâ€™s disharmony caused by busyness, self-centered nature, the cold war, and the culture of silence. The change of Japanese family system into the family system Tanshin Setai is reflected in the life of one of the characters in the television drama â€œKazoku Kashimasuâ€. The representation of family rental business is reflected by a company called Family Romance founded by Shuji as the main character. The Family Romance is a rental business family which proved a service of rental family for a wedding reception, a commemoration of those who have died called Shinobukai, the purposes of school enrollment at the famous school, and for a protest to a school on cases of bullying. Keywords : sistem keluarga Jepang, persewaan keluarga, drama televisi, sosiologi sastra